P4_4 The Lunar Recession - Evans, Lawrence Edward John; Cherrie, Daniel; Tyler, Adam; Ingram, Luke (Physics Special Topics, 2014)
This article investigates the Moon's recession from the Earth. The semi-major axis at which the Moon will become tidally locked with the Earth is calculated, and is found to be 558,000 km. It was found that the period of the Earth-Moon system would be about 48 current days long at this time. Using the Moon's current rate of recession, it was estimated that this process would happen in about 4.6 Gyr.